Kecerdasan Kinestetik untuk Anak Usia Dini - Nurhayati Nurhayati; Nayla Rizka Irwani; Yasmina Fajri; Nurul Fadilah Ibrahim Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The ability to match thoughts with movement is a key component of kinesthetic intelligence, which is examined in this study in early childhood. This ability supports the development of motor, physical, emotional, and learning skills through firsthand experience. The research methodology employed by the researchers is a literature review that gathers information from a variety of sources, including journals, books, and related research.